Media Pembelajaran Pengenalan Sandi Semaphore Menggunakan Augmented Reality - Castaka Agus Sugianto; Aldy Noer Tjahyo (STMIK IKMI Cirebon, 2019)
Submission of Semaphore material at Mutiara 5 Lembang Middle School is available in the boy scout book and is only in the form of 2-dimensional images and can also be delivered by the scoutmaster. In this case the delivery of the material for the Semaphore still has shortcomings. Therefore this study aims to build visual learning media to convey information about semaphore code using augmented reality. In order to provide more detailed knowledge about semaphore code actively, creatively and educatively. It is expected that with the function of converting text into semaphore code, students can see the visualization of semaphore code movements in real time. So that this application can be a new tool in improving the semaphore code learning method than before in the form of books. By using the Multimedia Develpoment Life Cycle method, in the testing phase by distributing UAT to 25 scout students and one coach showed 86.5% of results stated very good.